PENGARUH PERSEPSI KEMUDAHAN TERHADAP MINAT GUNA MELALUI KEPERCAYAAN PADA PENGGUNA DOMPET DIGITAL GOPAY - Rifki Hanif (UNIVERSITAS PGRI MADIUN, 2022)
This study aims to examine the effect of trust as a mediation between perceived ease of use and interest in using the GoPay application among FEB students, Institut Asia Malang. This study uses quantitative research approach with path analysis. The type of research used is explanatory research with survey methods. Data obtained by distributing questionnaires to a sample of 40 student respondents obtained through accidental sampling. Based on the results of data analysis that has been carried out, it is known that the perception of convenience affects the interest to use through consumer trust. Meanwhile, the perceived convenience variable does not directly affect interest in use.